Debt maturity and family related directors: evidence from a developing market - Hussain, Hafezali Iqbal; Zainal Abidin, Irwan Shah; Ali, Azlan; Kamarudin, Fakarudin (Management Faculty, Czestochowa University of Technology, 2018)
This paper examines the debt maturity structures of Malaysian firms based on the presence of family-related directors (FRDs) on boards. The motivation is derived from the board composition literature, which highlights reforms taken place over the years in order to ensure proper governance mechanisms. Conversantly, debt maturities are also linked to reductions in agency costs whereby firms with short-term borrowings will be subject to greater levels of monitoring by markets. Furthermore, this reduces information asymmetry. Thus, the paper evaluates the effectiveness of FRDs in alleviating the agency problem by studying the trade-off of such presence on debt maturity structures. The study finds that firms with the presence of FRDs tend to opt for longer maturity structures. These points towards a substitution effect where firms with FRDs will not rely on short-term borrowing as a mechanism for reducing agency problems. The findings of the study are further validated given that the presence of FRDs is not motivated by firms matching strategy of assets versus liabilities. However, these firms also opt for long-term borrowing in order to mitigate potential liquidity problems. The study further documents that these firms face lower bankruptcy costs. Interestingly, the authors also document that FRD opt to lengthen maturity structures during periods of increase in share prices indicating that control by family members tend to take into consideration shareholders’ wealth maximization. The finding is valid given that most firms with FRD also tend to have significant ownership by families.